Aluminium uptake and translocation in Al hyperaccumulator Rumex obtusifolius is affected by low-molecular-weight organic acids content and soil pH - Vondráčková, Stanislava; Száková, Jiřina; Drábek, Ondřej; Tejnecký, Václav; Hejcman, Michal; Müllerová, Vladimíra; Tlustoš, Pavel (PloS one, 2015)
BACKGROUND AND AIMS: High Al resistance of Rumex obtusifolius together with its ability to accumulate Al has never been studied in weakly acidic conditions (pH > 5.8) and is not sufficiently described in real soil conditions. The potential elucidation of the role of organic acids in plant can explain the Al tolerance mechanism. METHODS: We established a pot experiment with R. obtusifolius planted in slightly acidic and alkaline soils. For the manipulation of Al availability, both soils were untreated and treated by lime and superphosphate. We determined mobile Al concentrations in soils and concentrations of Al and organic acids in organs. RESULTS: Al availability correlated positively to the extraction of organic acids (citric acid < oxalic acid) in soils. Monovalent Al cations were the most abundant mobile Al forms with positive charge in soils. Liming and superphosphate application were ambiguous measures for changing Al mobility in soils. Elevated transport of total Al from belowground organs into leaves was recorded in both lime-treated soils and in superphosphate-treated alkaline soil as a result of sufficient amount of Ca available from soil solution as well as from superphosphate that can probably modify distribution of total Al in R. obtusifolius as a representative of "oxalate plants." The highest concentrations of Al and organic acids were recorded in the leaves, followed by the stem and belowground organ infusions. CONCLUSIONS: In alkaline soil, R. obtusifolius is an Al-hyperaccumulator with the highest concentrations of oxalate in leaves, of malate in stems, and of citrate in belowground organs. These organic acids form strong complexes with Al that can play a key role in internal Al tolerance but the used methods did not allow us to distinguish the proportion of total Al-organic complexes to the free organic acids.
Keywords: Molecular Weight; biologický transport; Tissue Distribution; Rumex; látky znečišťující půdu; analýza hlavních komponent; molekulová hmotnost; koncentrace vodíkových iontů; Biological Transport; Citric Acid; hliník; kyselina citronová; Aluminum; Acetic Acid; Soil Pollutants; Principal Component Analysis; tkáňová distribuce; Hydrogen-Ion Concentration; Soil; kyselina oxalová; Oxalic Acid; půda; kyselina octová